2013
DOI: 10.1155/2013/742195
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and Spinal Mechanisms of Acupoint Sensitization Phenomenon

Abstract: This study was carried out on adult female Sprague-Dawley rats to observe the position, size, and sensitivity change of inflammatory reactions on body surfaces induced by colorectal import of inflammatory irritant mustard oil. Colorectal distension (CRD) was adopted as a visceral noxious stimulus to record the activities of spinal dorsal horn wide-dynamic range (WDR) neurons activities at spinal segments L1–L3. The study also observed the activations of WDR neurons by electro-acupuncture (EA) on acupoints of Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…The size and function of acupoints will vary along with the state of viscera. The so-called acupoint sensitization phenomenon is the specific reflection of visceral diseases through acupoints [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The size and function of acupoints will vary along with the state of viscera. The so-called acupoint sensitization phenomenon is the specific reflection of visceral diseases through acupoints [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many morphological studies observed the neuronal projections between spinal cord and SRD area [ 16 20 ], suggesting the existence of a neuronal circuit interconnecting the spinal cord and the medulla oblongata. In our previous studies [ 21 , 22 ], we observed that visceral inflammation could facilitate the responses of WDR and SRD neurons to acupoint stimulation and a linear relationship existed between the intensity of nociceptive stimulation to inner organs and the sensitivity of related acupoint. These findings suggest that the function of viscerosomatic convergence-facilitation at the spinal and medulla levels maybe related to acupoint sensitization phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…At some acupoints there appeared to be hypersensitivity towards temperature (heat sensitisation) or pain threshold (pain-sensitisation) under visceral pain. 9 25 But unlike those studies, we examined acupoints in patients with musculoskeletal pain in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have observed that visceral lesions result in changed pain perception of some particular acupoints on the body surface. 9 Ben et al assessed the phenomenon of experimental pain-sensitive points in patients with gastric ulcer or gastritis and found that some acupoints were more sensitive than other areas. 10 Nevertheless, whether acupoints are more sensitive in patients with musculoskeletal pain has not been described in detail in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have used animal models to explore mechanisms of pain sensitization. It is found that acupoints may be sensitized by visceral noxious stimuli and the sensitive degree of acupoints changed according to malfunction of internal organs . Myofascial trigger points (MTrPs) were proposed as a mechanism to explain musculoskeletal pain , and they may resemble acupoints in location and function.…”
Section: The Local Effects When Stimulating Acupointsmentioning
confidence: 99%